Pharmacokinetics/pharmacodynamics and therapeutic drug monitoring of ceftazidime/avibactam administered by continuous infusion in patients with MDR Gram-negative bacterial infections. (10th January 2023) - Fresan, D; Luque, S; Benítez-Cano, A; Sorlí, L; Milagro Montero, M; De-Antonio, M; Prim, N; Vega, V; Horcajada, J P; Grau, S
Abstract: Background: Therapeutic drug monitoring (TDM) of β-lactams in critically ill patients has been correlated with better clinical outcomes. Evidence on TDM of newer β-lactams such as ceftazidime/avibactam administered by continuous infusion (CI) is very limited. Objectives: To describe our experience with TDM of ceftazidime/avibactam and pharmacokinetic/pharmacodynamic (PK/PD) target attainment in patients with MDR bacterial infections. Clinical outcomes of ceftazidime/avibactam administered by CI were also assessed. Methods: Patients treated with ceftazidime/avibactam administered by CI and undergoing TDM of ceftazidime plasma concentrations were included. Blood samples were obtained as part of the TDM program. The PK/PD therapeutic target of ceftazidime/avibactam was defined as 100% f T > 4 × MIC of the causative pathogen, and 100% f T > 10 × MIC was considered overexposure. Dose changes were made according to the TDM results. Results: Thirty-one patients were included. Ceftazidime/avibactam total daily doses ranged from 1 g/0.25 g to 6 g/1.5 g. Twenty-six patients (83.9%) achieved a 100% f T > 4 × MIC, 15 (48.4%) of which were overexposed (100% f T > 10 × MIC). Dose reduction was suggested in 16/28 (57.1%) patients and dose maintenance in 12/28 (42.9%). Overall clinical cure was observed in 21 (67.7%) patients, and 18 of these (85.7%) achieved a 100% f T > 4 × MIC. Conclusions: Administering ceftazidime/avibactam by CI enabled the desired PK/PD target to be achieved in a large proportion of patients, even at lower doses than those recommended for a 2 h extended infusion. We suggest that the use of CI with TDM may be a useful tool for reducing initial doses, which could help to reduce antimicrobial-related adverse effects and treatment costs.